Comparison of the pervaporation separation of a water-acetonitrile mixture with zeolite-filled sodium alginate and poly(vinyl alcohol)-polyaniline semi-interpenetrating polymer network membranes - Naidu, B. V. K.; Bhat, S. D.; Sairam, M.; Wali, A. C.; Sawant, D. P.; Halligudi, Shivaraj B.; Mallikarjuna, N. N.; Aminabhavi, Tejraj M. (Journal of Applied Polymer Science, 2005)
The pervaporation (PV) separation performance of ZSM-5- and Na-Y-type zeolite-filled sodium alginate (NaAlg) membranes were compared with those of pure NaAlg and semi-interpenetrating polymer network (semi-IPN) membranes of poly(vinyl alcohol) (PVA) with polyaniline (PANI) for the dehydration of acetonitrile. The PV separation characteristics of the zeolite-filled membranes showed a dependence on the nature of the zeolites. The variation of the acidity function of the ZSM-5 zeolite had an influence on the flux and selectivity of the membranes when compared to unfilled membranes. The crosslinked membranes were characterized by differential scanning calorimetry, X-ray diffraction, scanning electron microscopy, and Fourier transform infrared spectroscopy. Increasing the PANI content of the semi-IPN network increased the separation selectivity. Among the NaAlg membranes, the plain NaAlg membrane showed the highest selectivity of 414 at 30 mass % water in the feed mixture, whereas the Na-Y- and ZSM-5 (40)-filled NaAlg membranes exhibited much lower values of selectivity, that is, 7.3 and 4.3, respectively for 30 mass % water in the feed. When the flux and selectivity data of ZSM-5 (250)-filled NaAlg membranes were compared with that of Na-Y- or ZSM-5 (40)-filled NaAlg membranes, a noticeable increase in the selectivity for the ZSM-5 (250)filled NaAlg membrane was observed, but a somewhat comparable flux was observed compared to the plain NaAlg membrane. For the first time, PANI was polymerized with PVA to yield a semi-IPN. The total flux and water flux increased systematically, whereas the selectivity decreased greatly from 251.87 to 5.95 with increasing amounts of water in the feed. (c) 2005 Wiley Periodicals, Inc.
Keywords: Diffusion; interpenetrating network (IPN); zeolites

Simultaneous conversion of methane and methanol into gasoline over bifunctional Ga-, Zn-, In-, and/or Mo-modified ZSM-5 zeolites - Choudhary, Vasant R.; Mondal, Kartick C.; Mulla, Shafeek Abdul Rashid (Angewandte Chemie-International Edition, 2005)
Keywords: gallium; heterogeneuos catalysis; methane activation; Molybdenum; zeolites

Claisen rearrangement of allyl phenyl ether over zeolites beta, mordenite and Y - Wagholikar, S. G.; Mayadevi, S.; Jacob, Nalini E.; Sivasanker, S. (Microporous and Mesoporous Materials, 2006)
The Claisen rearrangement of allyl phenyl ether (APE) to o-allylphenol was investigated over zeolites beta (BEA), mordenite (MOR) and Y (FAU) with different Si/Al ratios. Over the zeolite catalysts, the allylphenol cyclized to produce 2,3-dihydro-2-methyl benzofuran. Larger catalyst loading, higher reaction temperatures and longer run duration favored the formation of the ring compound. Conversion was small over MOR and FAU although they possessed higher acidity (as measured by the temperature programmed desorption of ammonia) compared to BEA. Studies using BEA revealed that the nature of the solvent influenced the reaction rate. The order of reactivity in the solvents was, benzene > EDC (1,2-dichloroethane) > toluene > TCE (1, 1,2,2-tetrachloroethane) >> ACN (acetonitrile). The intermediate allylphenol reacted with the aromatic solvents to produce byproducts when benzene and toluene were used as solvents. A kinetic analysis assuming first order series and parallel reactions is presented. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: allyl phenyl ether; allylphenol; Benzofuran; Claisen rearrangement; zeolites

Liquid phase alkylation of phenol with 1-octene over large pore zeolites - Wagholikar, Smita; Mayadevi, S.; Sivasanker, S. (Applied Catalysis A-General, 2006)
A comparative study is presented of the liquid phase alkylation of phenol with 1-octene over different zeolite catalysts: H-beta (BEA(15)), H-mordenite (MOR(11)) and H-USY (FAU(15)). A wide spectrum of monoalkylated products, identified as isomers of phenyl octyl ether (O-alkylate) and octyl phenol (C-alkylate), was formed in the reaction. The reaction was studied in detail over BEA(15), such studies included the influence of process variables such as temperature, reactant mole ratio, catalyst amount and alkali metal (K) poisoning on its performance in the alkylation reaction. A kinetic analysis of the reaction over BEA(15) was also carried out assuming a second order parallel reaction mechanism. The activity of the different catalysts for the reaction followed the order: BEA(15) > FAU(15) > MOR(11). The poisoning of BEA(15) with potassium resulted in a decrease in the catalyst activity concomitant with a decrease in the number of strong acid centres in the catalyst. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: 1-octene; alkyl phenols; Alkylation; phenol; zeolites

Theoretical study of N2O reduction by CO in Fe-BEA zeolite - Fischer, Gerd; Goursot, Annick; Coq, Bernard; Delahay, Gerard; Pal, Sourav (Chemphyschem, 2006)
Quantum mechanical (QM) and QM/molecular mechanics (MM) studies of the full catalytic cycle of N2O reduction by CO in Fe-BEA zeolite, that is, oxidation of BEA-Fe by NO and reduction of BEA-Fe-alpha O by CO, is presented. A large QM cluster, representing half of the channel of the BEA zeolite, is used. The contribution of the MM embedding to the calculated activation energies is found to be negligible. The minimum-energy paths for N2O decomposition and reduction with CO are calculated using the nudged elastic bond (NEB) method. Calculated band experimental activation energies ore in good agreement The two possible orientations for the gaseous molecules adsorbing on the Fe site that ore found lead to different activation energies.
Keywords: Density functional calculations; iron; nitrogen oxides; reaction mechanisms; zeolites

Acylation of anisole with long-chain carboxylic acids over wide pore zeolites - Wagholikar, S. G.; Niphadkar, P. S.; Mayadevi, S.; Sivasanker, S. (Applied Catalysis A-General, 2007)
The acylation of anisole with long-chain carboxylic acids (hexanoic, octanoic and decanoic) has been studied over three large pore zeolites-beta (BEA), faujasite (FAU) and mordenite (MOR). The acylation of anisole with the long chain acids produced mainly the ketone (4-methoxy phenyl alkyl ketone) and small amounts of the ester (phenyl alkanoate). The results revealed the reaction to be influenced by the type of zeolite and its Si/Al ratio (acidity) besides the chain length (carbon number) of the carboxylic acid. In the acylation of anisole with hexanoic acid, the activity of the zeolites increased with dealumination as it led to the generation of mesopores that resulted in a decrease in diffusion resistance of the zeolites. The reactivity of the acids in the acylation reaction was found to decrease with increase in the carbon number. The experimental data have been fitted into a pseudo first order kinetic model. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Acylation; Anisole; decanoic acid; hexanoic acid; octanoic acid; zeolites

Synthesis and characterization of NCL-5, NCL-6 and NCL-7: new zeolites enriched with polymorph B of the BEA family - Kadgaonkar, Mahesh D.; Kasture, Mahesh W.; Bhange, Deu S.; Joshi, Praphulla N.; Ramaswamy, Veda; Gupta, Narendra M.; Kumar, Rajiv (Microporous and Mesoporous Materials, 2007)
The synthesis of all-silica analogs of polymorph B-enriched zeolites of the BEA family denoted as NCL-5, NCL-6 and NCL-7 was realized hydrothermally at lower water content in fluoride medium using perchloric acid as promoter and terraethylammonium hydroxide as template. The present article explains the effect of different synthesis parameters on NCL-5, NCL-6 and NCL-7. The samples were characterized using XRD, low temperature N-2-adsorption, Si-29 MAS NMR and FTIR spectroscopy. The phase composition of the structures was derived using simulated patterns for the random intergrowths of polymorphs A and B using DIFFaX Code. The stacking direction c' is perpendicular to the a'b' plane of the layer. The phase composition of polymorph B derived using DIFFaX code was found to be 90-95%. 70-75% and 60-65% in NCL-5, NCL-6 and NCL-7, respectively. The gradual decrease of polymorph B concentration in these samples showed a correlation with the decrease in water/SiO2 molar ratio in gel. The framework FTIR spectral analysis of NCL-5 and all-silica-beta supported the postulation that significant enrichment of polymorph B in NCL-5 compared to that in all-silica-beta, as indicated by the relative intensities of pair of bands at 1097 and 1018 cm(-1) and 460 and 423 cm(-1) vibrations, leads to more tortuous channel structure associated with polymorph B. (C) 2007 Elsevier Inc. All riahts reserved.
Keywords: BEA family; NCL-5; NCL-6; NCL-7; polymorph B enrichment; synthesis; zeolites

One-Pot method for the selective conversion of hemicellulose from crop waste into C5 sugars and furfural by using solid acid catalysts - Sahu, Ramakanta; Dhepe, Paresh Laxmikant (Chemsuschem, 2012)
We present a solid-acid catalyzed one-pot method for the selective conversion of solid hemicellulose without its separation from other lignocellulosic components, such as cellulose and lignin. The reactions were carried out in aqueous and biphasic media to yield xylose, arabinose, and furfural. To overcome the drawbacks posed by mineral acid methods in converting hemicelllulose, we used heterogeneous catalysts that work at neutral pH. In a batch reactor, these heterogeneous catalysts, such as solid acids (zeolites, clays, metal oxides etc.), resulted in >90% conversion of hemicellulose. It has been shown that the selectivity for the products can be tuned by changing the reaction conditions, for example, a reaction carried out in water at 170 degrees C for 1 h with HBeta (Si/Al=19) and HUSY (Si/Al=15) catalysts gave yields of 62 and 56% for xylose and arabinose, respectively. With increased reaction time (6 h) and in presence of only water, HUSY resulted in yields of 30% xylose+arabinose and 18% furfural. However, in a biphasic reaction system (water+p-xylene, 170 degrees C, 6 h) yields of 56% furfural with 17% xylose+arabinose could be achieved. It was shown that with the addition of organic solvent the furfural yield could be increased from 18 to 56%. Under optimized reaction conditions, >90% carbon balance was observed. The study revealed that catalysts were recyclable with a 20% drop in activity for each subsequent run. It was observed that temperature, pressure, reaction time, substrate to catalyst ratio, solvent, and so forth had an effect on product formation. The catalysts were characterized by means of X-ray diffraction, temperature-programmed desorption of NH3, inductively coupled plasma spectroscopy, elemental analysis, and solid-state NMR (Si-29, Al-27) spectroscopy techniques.
Keywords: analytical methods; Biomass; carbohydrates; heterogeneous catalysis; zeolites

Glycerol etherification using n-butanol to produce oxygenated additives for biodiesel fuel over H-beta zeolite catalysts - Nandiwale, Kakasaheb Y.; Patil, Shivraj E.; Bokade, Vijay V. (Energy Technology, 2014)
The catalytic etherification of glycerol has been systematically studied in batch process by using n-butanol to produce oxygenated additives for biodiesel fuels over various solid-acid catalysts, such as H-beta zeolite, ZSM-5, K10, etc.. The present work includes a detailed study of the optimization of the etherification process parameters, such as catalyst loading (7-20 wt% of glycerol), molar ratio of glycerol/n-butanol (1: 6 to 1: 15), speed of agitation (100-400 rpm), reaction temperature (413-453 K), and reaction time (0.5-4 h) in view of maximizing the glycerol conversion and selectivity towards mono-butyl-glycerol ether (ME). The catalyst reusability was studied using the optimized process parameters. Amongst the studied catalysts, the H-beta zeolite was found to be the most promising for the etherification of glycerol with glycerol conversion of 55% and a 98% selectivity towards ME formation. The H-beta zeolite was found to be an active and stable catalyst for up to 4 cycles. The use of n-butanol as alkylating agent is presented for first time, to the authors knowledge. The reaction was performed at milder operating conditions (0.5 MPa) than previously reported (2 MPa). A kinetic model was developed for the etherification reaction and the data obtained at optimized process parameters was used to calculate the kinetic parameters. The reaction rate constants at different reaction temperatures, activation energies, and pre-exponential factors were obtained for the etherification reaction with an accuracy of R-2 > 0.989.
Keywords: biofuels; catalysis; etherification; fuel additives; zeolites

Insights into adsorption of various gases on extra-framework cations of zeolite: a dispersion corrected DFT study on zeolite cluster models with Li plus , Na plus and K plus ions - Devasia, George; Kumar, Ravi; Vaval, Nayana; Krishnamurty, Sailaja (Microporous and Mesoporous Materials, 2023)
Design of an economical and sustainable gas separation material is relevant in several industrial processes. Zeolites with tunable pore sizes are ideal molecular sieves of many gases. The adsorption centers of these molecular sieves are extra-framework Lewis acid centers. In this study, we attempt to delineate the electronic properties of such centers (Li+, Na+ and K+) and their sorption properties towards N2, O2, CO, CO2 and H2. Negative framework of zeolites are modeled using different cluster models that present distinct electronic environment and role of this environment on the Lewis acidity of the cation. The sorption property towards different gases is evaluated using dispersion corrected DFT studies. The results obtained are benchmarked for one of the studied model using CCSD calculations. The results indicate that while the local environment modulates the adsorption properties, the relative adsorption properties between different ions follow the same order irrespective of the type of negative framework modeled. This reveals that intrinsic atomic properties of the charge compensating cations drive the sorption properties of the zeolites. Adsorption energies compounded with the analysis of IR stretching frequencies of the adsorbed gases reveals that Li centers shows molecular adsorption (charge donation to the cationic centers) towards N2 as compared to O2 and towards CO2/CO as compared to H2, demonstrating the applicability of Li-Zeolites as ideal membranes for oxygen concentrators and syngas separation. These adsorption studies are ratified by the BOMD simulations at 300 K, where H2 and O2 desorbs while N2, CO and CO2 remains adsorbed to the cationic site.
Keywords: BOMD simulation; CO/CO2/H2 separation; Extra-framework cation; N2/O2 separation; zeolites

Investigation of the effect of zeolite supports and the role of W-species for one-pot catalytic conversion of cellulose to ethylene glycol: theoretical & experimental studies. - Sreekantan, Sreejith; Singh, Chandrodai Pratap; Krishnamurty, Sailaja; Marimuthu, Banu (Chemistry-An Asian Journal, 2023)
Endeavors were made to study the influence of various zeolite (HY, NaY, NaZSM-5 and HZSM-5) supports with (Al)-Ni-W metal combination catalysts for the ethylene glycol (EG) production, selectively from cellulose. From the experimental results ZSM-5 (NaZSM-5/73.3% & HZSM-5/67.7%) support is superior over HY & NaY support in selective EG production from cellulose. It was understood that W- species with oxygen vacancies (WO3-x, XPS analysis) plays an important role in producing the glycolaldehyde (GA) intermediate (via C-C cleavages), which on hydrogenation over Ni- sites selectively produce EG. Further, the studies based on the Density Functional Theory (DFT) were conducted to substantiate the involvement of the WO3-x species in the reaction. The adsorption energies and structural changes establish that the C-2-C-3 bond of the glucose elongates and thereby activates on adsorbing to WO3-x sites supporting the formation of GA. Activation of GA on Ni- sites is distinguished by an increase of 0.1 angstrom in C=O bond length, which facilitates the hydrogenation of C=O resulting in EG. The reaction pathway is explained through an analysis of CDD and DOS.
Keywords: Cellulose hydrogenolysis; DFT studies; ethylene glycol; zeolites

Continuous flow synthesis of hierarchical low silica X zeolite - Adarsh, V. K.; Shrotri, Aadesh R.; Birje, Amit R.; Nandanwar, Sachin U. (Materials Today Communications, 2024)
Zeolites, renowned for their versatile applications in catalysis, adsorption, and ion exchange, have long been synthesized using conventional batch processes. However, the inherent limitations of these methods, such as resource-intensive conditions and inconsistent product quality, underscore the need for a sustainable and efficient approach. In this study, a continuous flow synthesis process was established for the synthesis of industrially important low silica X (LSX) zeolite using a tubular reactor. The synthesis gel was subjected to aging for 5 days at room temperature to facilitate nucleation and crystal growth combined with the fast-heating rate in a tubular reactor at 363 K & 1.1 atm., which in turn produces LSX after 40 min. The synthesized product was confirmed by the XRD, FE-SEM, EDS, XRF, TEM, and N2 adsorption-desorption; the data was compared with the LSX sample synthesized by batch process. The result implies that LSX prepared by continuous flow has a pure phase of LSX with the hierarchical structure, which provides better adsorption capacity of CO2 at 298 K up to 20 bar. Due to continuous flow synthesis, the crystallization time was reduced and faster kinetics which may be helpful for scale-up the process for LSX synthesis.
Keywords: Adsorption; Carbon dioxide; continuous flow; Low silica X; Tubular reactor; zeolites